Cardiovascular magnetic resonance demonstration of the spectrum of morphological phenotypes and patterns of myocardial scarring in Anderson-Fabry disease. Issue 1 (December 2016) - Deva, Djeven; Hanneman, Kate; Li, Qin; Ng, Ming; Wasim, Syed; Morel, Chantal; Iwanochko, Robert; Thavendiranathan, Paaladinesh; Crean, Andrew
Abstract Background Although it is known that Anderson-Fabry Disease (AFD) can mimic the morphologic manifestations of hypertrophic cardiomyopathy (HCM) on echocardiography, there is a lack of cardiovascular magnetic resonance (CMR) literature on this. There is limited information in the published literature on the distribution of myocardial fibrosis in patients with AFD, with scar reported principally in the basal inferolateral midwall. Methods All patients with confirmed AFD undergoing CMR at our center were included. Left ventricular (LV) volumes, wall thicknesses and scar were analyzed offline. Patients were categorized into 4 groups: 1) no wall thickening; 2) concentric hypertrophy; 3) asymmetric septal hypertrophy (ASH); and 4) apical hypertrophy. Charts were reviewed for clinical information. Results Thirty-nine patients were included (20 males [51 %], median age 45.2 years [range 22.3–64.4]). Almost half (17/39) had concentric wall thickening. Almost half (17/39) had pathologic LV scar; three quarters of these (13/17) had typical inferolateral midwall scar. A quarter (9/39) had both concentric wall thickening and typical inferolateral scar. A subgroup with ASH and apical hypertrophy (n = 5) had greater maximum wall thickness, total LV scar, apical scar and mid-ventricular scar than those with concentric hypertrophy (n = 17, p < 0.05). Patients with elevated LVMI had more overall arrhythmia (p = 0.007) more ventricular arrhythmia (p = 0.007) and sustained ventricular tachycardia (p = 0.008). Conclusions Concentric thickening and inferolateral mid-myocardial scar are the most common manifestations of AFD, but the spectrum includes cases morphologically identical to apical and ASH subtypes of HCM and these have more apical and mid-ventricular LV scar. Significant LVH is associated with ventricular arrhythmia.